Investigation of the combined methods of filtration, copper oxide nanoparticles and microalgae on palm oil mill effluent (POME) treatment - Phang, You Kang (2023)
In the developing country like Malaysia, the demand of freshwater and water pollutions has become the issues concerned by the society. The water pollution caused by the agroindustry especially the palm oil industry requires a long duration to recover. The research on palm oil mill effluent (POME) is to discover the alternative treatment method that can reduce current treatment time, at the same time improve the water quality effectively. In this research, the POME was undergone pre-treatment by passing through a conventional filtration system set up using coarse sand, fine sand and activated carbon. Then, the filtered POME was treated with heterogeneous photocatalytic degradation. The copper oxide nanoparticles (CuO NPs) photocatalyst used for degrading the POME was greenly synthesized using papaya peel extract and copper (II) nitrate trihydrate salt. The green-synthesized CuO NPs were characterized with different analytical methods such as ultraviolet-visible (UV-vis) spectroscopy, iii Raman spectroscopy, transmission electron microscopy (TEM), field emission scanning electron microscopy (FE-SEM) and other instrumentations. The analysis revealed that the CuO NPs were able to degrade 66 % of POME under ultraviolet light irradiation. After photodegradation, the treated POME was polished with two different microalgae which were Chlorella vulgaris and Chlamydomonas reinhardtii, respectively. The growth of both microalgal were observed without dilution of the pre-treated POME. As a result, the combination of these physical, chemical and biological treatment able to remove more than 90 % of colour, phosphate and ammoniacal nitrogen and remove more than 80 % of chemical oxygen demand (COD) and biochemical oxygen demand (BOD). The phytotoxicity of the treated POME was studied by monitoring the growth of mung bean seeds. The phytotoxicity of the treated POME was reduced 95 % after undergone the combination treatments.